Continuous shaft drawtwister for nylon (1946)
Close-up view of a continuous shaft drawtwister used during the early stages of nylon production and research at DuPont. As part of the cold-drawing process, drawtwisters were used to stretch the nylon filaments following extrusion. In this version, a supply of undrawn yarn was loaded into a feed roll, around a draw pin, through a continuous shaft, and through a rubber draw roll before finally being wound onto a bobbin.
Keywords: Nylon; Polymers; Nylon--Testing; E.I. du Pont de Nemours & Company; Machinery